The social economy of ageing : Job quality and pathways beyond the labour market in Europe - Pollak, Catherine (Paris, 2011)
"This article analyses the effect of job quality on pathways to productive activities of older workers in Europe. Using comparative panel data from SHARE, we analyse the medium term effects of working conditions of workers aged 50-64 on three participation outcomes (staying in employment, participating in social activities and providing informal care) with a trivariate probit model. Several aspects of job quality appear to play a role for participation in society as a whole, including participation in social activities. Care-giving on the other hand appears independent from the considered job quality indicators, but very gender specific. However, trade-offs between full time work and care activities appear in some cases. Therefore, better working conditions and the opportunity for work time arrangements should be developed if one aims to foster participation of older workers in the society."